The impact of Caulerpa lentillifera seaweed-based coatings on physicochemical characteristics and shelf longevity of fruits and vegetables - Nuraqilah Syamimi Mat Jauilah; Rovina Kobun; Wahidatul Husna Zuldin; Sarifah Supri; Patricia Matanjun; Luh Suriati (Tech Science Press, 2025)
Food breakdown during storage and transit greatly adds to worldwide food waste. Biodegradable edible coatings derived from natural sources provide a sustainable method to extend the shelf life and preserve the freshness of fresh fruit. This study explores the potential of the readily available and nutrient-rich seaweed, Caulerpa lentillifera, as a base material for edible coatings that can enhance the shelf life and maintain the physicochemical properties of fruits and vegetables. Caulerpa lentillifera, a marine macroalga renowned for its unique biochemical composition, presents a promising avenue for developing sustainable bio-coatings to improve the post-harvest quality of fresh produce. Biodegradable edible coatings derived from natural sources provide a sustainable method to extend the shelf life and preserve the freshness of fresh fruit. This study is aimed at exploring the potential of Caulerpa lentillifera, a nutrientdense green seaweed, as a foundational material for creating edible coatings to enhance the post-harvest quality of fruits and vegetables. Various Caulerpa lentillifera-derived coating formulations were developed and applied to specific fruits and vegetables. The coated samples were maintained under controlled conditions and assessed for alterations in physicochemical parameters, including weight loss, hardness, colour, and microbial proliferation. The optimised coating formulation markedly diminished weight loss, postponed ripening, and maintained firmness and colour relative to uncoated controls. The coating demonstrated promising antibacterial properties, aiding in the extension of shelf life. Coatings derived from Caulerpa lentillifera offer a viable, environmentally sustainable alternative to synthetic preservatives, facilitating the advancement of sustainable food preservation technology.